When Idioti (Idiotic) Becomes “Fluffy”: Translation Students and the Avoidance of Target-language Cognates - Malkiel, Brenda (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2009)
AbstractCognate translation is neither a simple nor a straightforward matter. Given the risk that a word that appears to be a true cognate may actually be a false cognate, and given the sometimes fuzzy boundary between true and false cognates, translators and translation students have been shown to “play it safe” by casting around for noncognate translations for true cognates, rather than choose the obvious cognate translation. Here we ask whether translation students avoid cognate translations even when the target-language cognate is both accurate and appropriate and whether this phenomenon is related to fear of false friends. The findings indicate that translation students do seek out noncognate translations and that performance on true cognates correlates with performance on false cognates.